Wet distiller’s grains with solubles in beef finishing diets comprised of steam-flaked or dry-rolled corn - May, M.L.; Quinn, M.J.; Drouillard, James S.; Walker, Charles E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The purpose of this experiment was to determine optimal levels of distiller’s grains in finished diets with steam-flaked corn or dry rolled corn. Distiller’s grains have been used extensively in regions of the country in which dry-rolled and high-moisture grains are prevalent. Production of fuel ethanol is now expanding into the High Plains, where feedlots more commonly use steam flaking. The cost to produce flaked corn is higher than the cost to produce dry rolled corn, and with rising energy costs (especially natural gas), this spread is becoming more dramatic. Comparing the use of wet distiller’s grains fed in conjunction with these grains provides useful information concerning optimum use level.
Keywords: Beef; Cattle; Distillers grains; Steam flaking; Dry-rolled corn